Search 82,201 tutors
FIND TUTORS
Ask a question
0 0

how do you solve 3(x+1) - 5x = 12 - (6x -7)

Tutors, please sign in to answer this question.

1 Answer

3( X+1) - 5 X = 12 - ( 6X - 7 )
 
  1st step : Simplify both sides:
 
   3X + 3 - 5X = 12 - 6X + 7 
 
   -2X + 3 = 19 - 6x 
 
  2nd step : Move variables to one side and Constants to other, and simplify both sides.
    
     -2X +6X = 19 -3
 
        4X = 16
 
     3rd Step: Solve for variable , by dividing both sides by coefficient of the variable
 
      X =4
 
      This 3 steps must be followed to solve any linear equation of single variable.